Association of soluble urokinase plasminogen activator receptor and epidermal growth factor with histopathological findings of kidney biopsy: a single-center study - Eman Nagy; Ahmed Almenshawy; Mostafa Abdelsalam; Ahmed M. Abd Elwahab; Ola M. Gharbia; Fatma El-Husseiny Moustafa; Nagy Sayed Ahmed; Nora A. Khreba (BMC Nephrology)
Abstract Background Despite the crucial role of kidney biopsy in the management of various kidney diseases, it has inherent limitations. Therefore, the search for non-invasive biomarkers as alternative diagnostic and prognostic tools is warranted. The aim of this study was to assess the association between soluble urokinase plasminogen activator receptor (suPAR) and epidermal growth factor (EGF) levels and various histopathological findings in patients undergoing kidney biopsy. Methods This cross-sectional study involved patients who underwent kidney biopsies over a period of nine months. On the day of the biopsy, sociodemographic, clinical, and routine laboratory data were collected from patients’ medical records. Urine samples were obtained for measurement of urinary suPAR, EGF, and creatinine levels. Kidney biopsies were reviewed and interpreted by an expert nephropathologist. Results A total of 82 patients (36 males) with a mean age of 36 years were included. The most common histopathological diagnosis was lupus nephritis (30.5%), followed by end-stage kidney disease (12%). Glomerulosclerosis (GS), tubular atrophy (TA), and interstitial fibrosis (IF) were present in 66%, 62%, and 74% of patients, respectively. Additionally, tubular injury, detached podocytes, and vascular fibrointimal thickening were observed in 30%, 5%, and 22% of patients, respectively. Both suPAR and EGF levels showed no statistically significant differences among varying degrees of GS, TA, and IF. However, urinary suPAR/creatinine was significantly higher in patients with tubular injury than in those without (p = 0.003). Its cut-off value to predict tubular injury was 0.08 with moderate sensitivity and specificity. Urinary EGF/creatinine was significantly lower in patients with detached podocytes than in those without (p = 0.028), whereas it was significantly higher in patients with vascular fibrointimal thickening than in those without (p = 0.043). Its cut-off value to predict vascular fibrointimal thickening was 0.88 with low-to-moderate sensitivity and moderate specificity. Conclusions Both urinary suPAR/creatinine and urinary EGF/creatinine ratios were not associated with either glomerulosclerosis or IF/TA, and therefore, cannot substitute for kidney biopsy in the assessment of kidney fibrosis. Higher urinary suPAR was associated with tubular injury, suggesting its potential link with acute tubular damage. In contrast, lower urinary EGF levels were found to be associated with podocyte detachment. Additionally, increased urinary EGF was associated with vascular fibrointimal thickening, suggesting a possible role in vascular remodeling. These findings highlight associations that warrant further investigation in longitudinal studies.